Esophageal Obstruction from Food Bolus Impaction Successfully Managed with the “Upright Posture, Chin Tuck, Double Swallow” Maneuver: A Case Report - Matthias Barden; Michael E. Schwartz (Clinical Practice and Cases in Emergency Medicine)
Introduction: An attempt at medical management is often the initial step in addressing esophageal obstruction from an impacted food bolus. Medical management, however, has limited success and often requires urgent endoscopy. We present a case in which standard medical treatment failed, but a swallowing augmentation maneuver resolved the obstruction. Case Report: A 67-year-old female presented with esophageal obstruction after eating steak. Transfer to higher level of care for endoscopy was initiated; however, the receiving gastroenterologist suggested an “upright posture, chin tuck, double swallow” maneuver. This immediately resolved the patient’s symptoms, and she was discharged home. Conclusion: This case suggests a novel, non-endoscopic technique for esophageal obstruction from food bolus impaction.